How Hypertension Affects Heart Metabolism - Polak-Iwaniuk, Agnieszka; Harasim-Symbor, Ewa; Gołaszewska, Karolina; Chabowski, Adrian (Frontiers in Physiology, 2019)
Hypertension is one of the most frequently observed cardiovascular diseases, which precedes heart failure in 75% of its cases. It is well established that hypertensive patients have whole body metabolic complications such as hyperlipidemia, hyperglycemia, decreased insulin sensitivity or diabetes mellitus. Since myocardial metabolism is strictly dependent on hormonal status as well as substrate milieu, the above mentioned disturbances may affect energy generation status in the heart. Interestingly, it was found that hypertension induces a shift in substrate preference toward increased glucose utilization in cardiac muscle, prior to structural changes development. The present work reports advances in the aspect of heart metabolism under high blood pressure conditions, including human and the most common animal models of hypertension.